2002
DOI: 10.1021/jp014618m
|View full text |Cite
|
Sign up to set email alerts
|

Interface Effects for Cu, CuO, and Cu2O Deposited on SiO2 and ZrO2. XPS Determination of the Valence State of Copper in Cu/SiO2 and Cu/ZrO2 Catalysts

Abstract: Copper and copper oxides (Cu2O and CuO) have been deposited by evaporation of copper and subsequent oxidizing treatments, on the surface of flat SiO2 and ZrO2 substrates. Large variations of several eVs have been found in the values of the Cu 2p3/2 binding energy (BE) and Auger parameter (α‘) of copper as a function of the amount of deposited metallic copper or copper oxides. The magnitude of the changes was also dependent on the type of support upon which the experiment was carried out. These changes have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
302
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(350 citation statements)
references
References 50 publications
42
302
1
5
Order By: Relevance
“…The coexistence of Cu and Cu 2 O in the synthesized material was also confirmed by use of XRD. The peak at 933.8 eV is due to CuO, although it is slightly higher than the reported energy of CuO (933.7 eV) (Wagner et al, 1979), it agrees well with other values reported for CuO surface phase (Wagner et al, 1979;Espinós et al, 2002;Zhu et al, 2004;Wang et al, 2003Wang et al, 2002Xu et al, 1999;Hui et al, 2002;Brookshier et al, 1999;Fernando et al, 2002). The, three peaks of 530.2, 531.6, 533.6 eV observed in the O1s spectrum (Fig.…”
Section: Characterization and Properties Of Adsorbentssupporting
confidence: 89%
See 1 more Smart Citation
“…The coexistence of Cu and Cu 2 O in the synthesized material was also confirmed by use of XRD. The peak at 933.8 eV is due to CuO, although it is slightly higher than the reported energy of CuO (933.7 eV) (Wagner et al, 1979), it agrees well with other values reported for CuO surface phase (Wagner et al, 1979;Espinós et al, 2002;Zhu et al, 2004;Wang et al, 2003Wang et al, 2002Xu et al, 1999;Hui et al, 2002;Brookshier et al, 1999;Fernando et al, 2002). The, three peaks of 530.2, 531.6, 533.6 eV observed in the O1s spectrum (Fig.…”
Section: Characterization and Properties Of Adsorbentssupporting
confidence: 89%
“…The, three peaks of 530.2, 531.6, 533.6 eV observed in the O1s spectrum (Fig. 4C) are consistent with the broad peak of O1s, the peak at 530.2 eV is consistent with O1s of Cu 2 O that have been reported previously, which are in the range of 530.0-530.7 eV (Wagner et al, 1979;Espinós et al, 2002;Zhu et al, 2004;Wang et al, 2003;Wang et al, 2002). O1s in CuO appears at 533.6 eV and the peak at 531.6 eV was assigned to other oxygen components such as OH, H 2 O and species of carbonate on the surface.…”
Section: Characterization and Properties Of Adsorbentssupporting
confidence: 89%
“…Two well defined satellite peaks associated with the Cu 2p 3/2 lines at 940.6 and 943.3 eV were also observed. The shake-up satellites are associated with Cu(II), [41,43,44]. Moreover, the Cu 2p peaks were broader with a shoulder.…”
Section: Xpsmentioning
confidence: 95%
“…On the other hand, the as-prepared SnO 2 :CuO samples had these signals at 486.5 and 530.3 eV, respectively, which were 0.2 eV lower than those of the pure SnO 2 sample. The agglomeration of SnO 2 on the addition of dopants has been reported to result in a decrease in the binding energy of SnO 2 [41]. The decrease in the binding energy (BE) of Sn 3d 5/2 in SnO 2 :CuO has also been ascribed to the presence of a CuO surface layer [7], suggesting that CuO is dispersed as fine particles on the surface of SnO 2 particles.…”
Section: Xpsmentioning
confidence: 99%
“…They are only slightly broadened in the range from ΔE = 0.65 to 0.9 eV which is not explicitly shown in the graph. The relatively large shift of the Cu peaks could be explained by the formation of Cu(II), but additional satellite peaks typical for an oxidation state of II are very weak [22]. However, the Cu2p and CuLMM based modified Auger parameter α increases from 1849.3 for the bare absorber to 1850.2 for the Na-treated CIGSe, indicating the transition of Cu(I) to a species that is closer to Cu(II).…”
Section: Resultsmentioning
confidence: 97%